Microwave assisted quaternization of poly(4-vinylpyridine) with 1-bromohexane - Topuzogullari, Murat (SPRINGER, 2018)
Quaternization reaction is a well-known technique and can be applied to obtain functional polycations. If quaternization agents used in this reaction contain more than 4 carbons, it can take days or weeks to reach high degrees in quaternization. In the study, microwave heating was used to increase the reaction rate. Kinetics of microwave-assisted quaternization of poly(4-vinylpyridine) with 1-bromohexane was investigated by varying the reaction conditions, such as solvent, temperature, molar ratio of components and concentrations. In less than 1 h, quaternization degree of poly(4-vinylpyridine) reached higher than 80% values in DMF and DMSO with microwave heating at 80 degrees C. Higher polymer concentration and molar ratio of N1-bromohexane/N4-vinylpyridine also increased the reaction rate. It was demonstrated that microwave heating can be applied to increase the quaternization reaction rate. Very short reaction times as low as minutes may allow quaternization reaction to be used in more studies for novel functional polycations.
Keywords: Polycation; Quaternization; Microwave; PYRIDINE); KINETICS; ALKYLATION; MECHANISM; Polymer Science